European longitudinal study on the relationship between adolescents' alcohol marketing exposure and alcohol use. (2nd August 2016) - de Bruijn, Avalon; Tanghe, Jacqueline; de Leeuw, Rebecca; Engels, Rutger; Anderson, Peter; Beccaria, Franca; Bujalski, Michał; Celata, Corrado; Gosselt, Jordy; Schreckenberg, Dirk; Słodownik, Luiza; Wothge, Jördis; et al.
Abstract: Background and aims: This is the first study to examine the effect of alcohol marketing exposure on adolescents' drinking in a cross‐national context. The aim was to examine reciprocal processes between exposure to a wide range of alcohol marketing types and adolescent drinking, controlled for non‐alcohol branded media exposure. Design: Prospective observational study (11–12‐ and 14–17‐month intervals), using a three‐wave autoregressive cross‐lagged model. Setting: School‐based sample in 181 state‐funded schools in Germany, Italy, Netherlands, Poland. Participants: A total of 9075 eligible respondents participated in the survey (mean age 14 years, 49.5% male. Measurements: Adolescents reported their frequency of past‐month drinking and binge drinking. Alcohol marketing exposure was measured by a latent variable with 13 items measuring exposure to online alcohol marketing, televised alcohol advertising, alcohol sport sponsorship, music event/festival sponsorship, ownership alcohol‐branded promotional items, reception of free samples and exposure to price offers. Confounders were age, gender, education, country, internet use, exposure to non‐alcohol sponsored football championships and television programmes without alcohol commercials. Findings: The analyses showed one‐directional long‐term effects of alcohol marketing exposure on drinking (exposure T1 on drinking T2: β = 0.420 (0.058), P  < 0.001, 95% confidence interval (CI) = 0.324–0.515; exposure T2 on drinking T3: β = 0.200 (0.044), P  < 0.001, 95% CI = 0.127–0.272; drinking T1 and drinking T2 on exposure: P  > 0.05). Similar results were found in the binge drinking model (exposure T1 on binge T2: β = 0.409 (0.054), P  < 0.001, 95% CI = 0.320–0.499; exposure T2 on binge T3: β = 0.168 (0.050), P  = 0.001, 95% CI = 0.086–0.250; binge T1 and binge T2 on exposure: P  > 0.05). Conclusions: There appears to be a one‐way effect of alcohol marketing exposure on adolescents' alcohol use over time, which cannot be explained by either previous drinking or exposure to non‐alcohol‐branded marketing.